Livability of Urban Public Spaces in Northern Swedish Cities : The Case of Umeå - Costamagna, Federico; Lind, Rebecka; Stjernström, Olof (Planning Practice & Research, 2019)
This study explores how winter conditions are taken into accountin urban planning in the city of Umea in northern Sweden. Snow and harsh winter conditions are to some extent considered inurban planning in most northern towns in Sweden. Besides that, snow and ice could also be elements in the city attracting people and contribute to the design of public spaces. Current plans and interviews with planners were complemented with participatory observations. The results show that public spaces designed for both winter and summer seasons are preferred.